Epileptic seizures as a manifestation of cow's milk allergy: a studied relationship and description of our pediatric experience. (December 2014) - Falsaperla, Raffaele; Pavone, Piero; Miceli Sopo, Stefano; Mahmood, Fahad; Scalia, Ferdinando; Corsello, Giovanni; Lubrano, Riccardo; Vitaliti, Giovanna
<x xml:space="preserve">Abstract</x> Adverse reactions after ingestion of cow's milk proteins can occur at any age, from birth and even amongst exclusively breast-fed infants, although not all of these are hypersensitivity reactions. The most common presentations related to cow's milk protein allergy are skin reactions, failure to thrive, anaphylaxis as well as gastrointestinal and respiratory disorders. In addition, several cases of cow's milk protein allergy in the literature have documented neurological involvement, manifesting with convulsive seizures in children. This may be due to CNS spread of a peripheral inflammatory response. Furthermore, there is evidence that pro-inflammatory cytokines are responsible for disrupting the blood–brain barrier, causing focal CNS inflammation thereby triggering seizures, although further studies are needed to clarify the pathogenic relationship between atopy and its neurological manifestations. This review aims to analyze current published data on the link between cow's milk protein allergy and epileptic events, highlighting scientific evidence for any potential pathogenic mechanism and describing our clinical experience in pediatrics.